Pengaruh Tekanan Situasional Terhadap Kecurangan Akuntansi Ditinjau dari Love Of Money - Pasek, Gede Widiadnyana (Jurnal Akuntansi Profesi, 2021)
This study aims to determine the differences in accounting fraud behavior between those given situational pressure treatment and those not given situational pressure treatment by controlling the love of money variable. This research is a quasi-experimental research with this research design only taking into account the final score. Collecting data in the study using a questionnaire in the form of cases. After the experiment ended the data were analyzed using covariance analysis. The results showed that there were differences in accounting fraud behavior between those that were given siteional pressure and those that were not given siteional pressure, then the results also showed that there were differences in accounting fraudulent behavior between those that were given siteional pressure and those that were not given situational pressure after the love of money variable was controlled.